Expectations and Reality in Surgical Rehabilitation of Cataract Patients - Lutsenko, N. S.; Isakova, O. A.; Rudycheva, O. A.; Kyrylova, T. S. (Transplantation and artificial organs, 2021)
The aim. To study the effect of surgical treatment of cataracts on the quality of life of patients and assess satisfaction with the results after implantation of a monofocal or multifocal intraocular lens (IOL), depending on the initial refraction. Materials and methods. We examined 140 patients (280 eyes) who underwent phacoemulsification with IOL (bilateral) according to the standard technique using multimodal anesthesia. The observation groups were divided depending on the initial type of refraction and the type of intraocular correction (mono- or multifocal IOL). The analysis of the results of surgical treatment of cataracts with IOL was assessed taking into account the initial refraction according to objective data, i.e. determination of distance and near visual acuity, and subjective data, i.e. the NEI-VFQ-25 quality of life questionnaire, patient questionnaire survey and assessment of the quality of vision in general, as well as distance, near, and night vision. Results and discussion. Before surgery, the mean values of indicators by all scales of the questionnaire of the quality of life related to the quality of vision ranged from 40 to 60 points and averaged 47 ± 0.5 points. After cataract surgery, the numerical indicator by each of the scales shifted to the range of 85 to 100 points. The difference in values by the scales “activity associated with distance vision” and “driving a car” was obtained. In patients with multifocal IOL, these indicators were lower compared with monofocal implantation. Dissatisfaction with distance vision was observed during the implantation of a multifocal IOL only in patients with hyperopia (12.5%), dissatisfaction with near vision was noted only in patients with myopia (16.7%), and no cases of dissatisfaction were observed in the group of patients with emmetropia. Analysis of night vision in patients with emmetropia also revealed the minimum percentage (2.5%) of cases of dissatisfaction in patients with hyperopia (5.0%) and the maximum in those with myopia (16.7%). Conclusions. IOL implantation is a single cataract treatment option that provides a high level of the patient’s satisfaction with the quality of life and visual functions. However, careful individual approach is required to select the type of implantable IOL, taking into account the patient’s needs and baseline refraction.